Talented footballers` identity in the age of professionalization of academies and sports school programmes in Norway - Belling, A. (Soccer & Society, 2026)
Professionalization of football talent development has had a widespread influence on the lives of Norwegian footballers. The football and educational aspects of their identities converge in their decisions on upper secondary education, where the option of a sports school programme significantly influences how talent development is practised. This article employed an abductive research protocol in a case study, conducting two rounds of interviews with five players and five coaches from an elite football club academy under-17 team. Drawing on Habermas` theory of communicative action, instrumental and communicative rationality are used to analyse and discuss how talented players` identities are influenced and used for clubs practice increasing role in narrowing down the players` options and thus decreasing their scope for communicative rationality. This limits their identity formation, as pursuing an SSP increasingly becomes the only path available to them.